La teoria dei generi letterari e la comparatistica: una ricognizione bibliografica ragionata (Comparatismi, 2025)
Since the 1970s, the notion of genre has re-emerged as a central concern in literary studies, shaping both artistic practice and critical theory. Scholars such as Ralph Cohen have described this shift as a generic turn, underscoring the performative nature of genre as a category that not only structures literary production and reception but also conditions theoretical and critical discourse. This article examines how the evolving concept of genre has influenced recent developments in comparative literature, a field particularly sensitive to transnational and cross-disciplinary approaches. By tracing key theoretical contributions and mapping their impact on the discipline, the study offers a critical bibliography that highlights the ways in which genre has guided literary theory and criticism throughout the past decades.
Keywords: Literary genre; Comparative literature; Generic turn; Literary theory; Genre theory